2014
DOI: 10.1523/jneurosci.1503-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

UV Irradiation Accelerates Amyloid Precursor Protein (APP) Processing and Disrupts APP Axonal Transport

Abstract: Overexpression and/or abnormal cleavage of amyloid precursor protein (APP) are linked to Alzheimer's disease (AD) development and progression. However, the molecular mechanisms regulating cellular levels of APP or its processing, and the physiological and pathological consequences of altered processing are not well understood. Here, using mouse and human cells, we found that neuronal damage induced by UV irradiation leads to specific APP, APLP1, and APLP2 decline by accelerating their secretase-dependent proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 88 publications
4
23
0
Order By: Relevance
“…These findings are in agreement with previous studies showing down-regulation of APP in response to both UV and camptothecin, though different mechanisms were proposed, with Cuesta et al [28] suggesting a p53-dependent reduction in the transcription of APP, whereas Almenar-Queralt et al [29] showed that the decrease in APP was due to secretase-mediated cleavage [28][29][30]. It is unclear whether loss of the Fe65-APP complex preceded the depletion of APP in cells or vice versa.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in agreement with previous studies showing down-regulation of APP in response to both UV and camptothecin, though different mechanisms were proposed, with Cuesta et al [28] suggesting a p53-dependent reduction in the transcription of APP, whereas Almenar-Queralt et al [29] showed that the decrease in APP was due to secretase-mediated cleavage [28][29][30]. It is unclear whether loss of the Fe65-APP complex preceded the depletion of APP in cells or vice versa.…”
Section: Discussionsupporting
confidence: 90%
“…Both b-and g-secretase can be found in axons and somatodendritic compartments (DeBoer et al, 2014;Sannerud et al, 2011), and both can be found in vesicles that also contain APP and kinesin-1 (Almenar-Queralt et al, 2014;Kamal et al, 2001). Co-localization of these components in the somatodendritic compartment may be regulated by synaptic activity (Das et al, 2013).…”
Section: App Trafficking and Processing: A Complex Itinerarymentioning
confidence: 99%
“…Axons and dendrites contain a diverse array of bidirectionally transported vesicles, generally ranging in size from a few tens to a few hundred nanometers. These include secretory vesicles 2527 , lysosomal vesicles 7, 28 , autophagosomes 29 , and vesicles containing amyloid precursor protein (APP) 3032 and mammalian prion protein 8 . Transport of these diverse neuronal cargo involves different motors, adaptors, and regulatory proteins, but in general, similar conceptual models have been applied to understanding the molecular mechanisms underlying bidirectional transport.…”
Section: Diversity In Bidirectional Transportmentioning
confidence: 99%